Culture and society : an introduction to cultural studies - Oswell, David (SAGE, 2006)
Grounding the reader in the foundations of cultural studies and cultural theory, David Oswell analyzes the central problems in the discipline: identity, body, economy, globalization and empire, and introduces the latest developments on materiality, agency, technology and nature. Culture and Society is an invaluable guide for students navigating the dynamic debates and intellectual challenges of cultural studies. Its breadth and unparallelled coverage of cutting-edge theory will also ensure that it is ready by anyone interested in questions of materiality and culture.